One-pot gram-scale synthesis of virucidal heparin-mimicking polymers as HSV-1 inhibitors. Issue 90 (21st October 2021) - Ahmadi, Vahid; Nie, Chuanxiong; Mohammadifar, Ehsan; Achazi, Katharina; Wedepohl, Stefanie; Kerkhoff, Yannic; Block, Stephan; Osterrieder, Klaus; Haag, Rainer
Abstract : A straightforward and gram-scale synthesis method was developed to engineer virucidal heparin-mimicking polymers as HSV-1 inhibitors. Abstract : A straightforward and gram-scale synthesis method was developed to engineer highly sulfated hyperbranched polyglycerol bearing sulfated alkyl chains. The compounds with shorter alkyl chains showed multivalent virustatic inhibition against herpes simplex virus type 1 (HSV-1), similar to heparin. In contrast, the compound with the longest alkyl chains irreversibly inhibited the virus.